ANALISIS KETAHANAN ABRASI MATERIAL OUTSOLE POLYURETHANE (PU) & NITRILE BUTADINE RUBBER (NBR) PADA SAFETY SHOES CHEETAH DI PT. X - Suherna Suherna; Patunru P; Maspah Maspah (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
Improved quality, strength and life time in terms of abrasion resistance on safety shoes outsole Cheetah material where the process use of some material has decreased in quality, besides due to usage factors, maintenance factors, and some of these materials also experience problems during use. This study is done to determine the abrasion resistance of each Outsole Polyurethane (PU) material and Nitrile Butadiene Rubber (NBR). Abrasion resistance test on the material method used the DIN Abrasion tester. Retrieval of data on outsole material was carried out on the outsole material with new conditions and that has been used in the field for a period of 1 year with a method of measuring abrasion resistance index and density of material. Calculation of average abrasion resistance for new Polyurethane (PU) type was 37 , 11 mm3 / year, while the average abrasion resistance for Polyurethane (PU) type that has been used for 1 year was 33.19 mm3 / year so that the difference is 3.92 mm3 / year or about 11% quality decrease of abrasion resistance. The average abrasion resistance with the new Nitrile Butadiene Rubber (NBR) type was 108.26 mm3 / year, the average abrasion resistance for Nitrile Butadiene Rubber (NBR) type with conditions already used in 1 year period was 107.44 mm3 / year so that the difference is 0.82 mm3 / year or about 1% decrease in quality decrease of abrasion resistance. Abrasion tolerance limits that have been set according to the SOP (Standard Operational Procedure) against abrasion resistance if SG ≥ 0.9 then the Abrasive Max is 150 and if SG ≤ 0.9 Then the Abrasive Max is 250.